GENDER INTERACTION EFFECT WITH MOTHER TONGUE MODEL OF INSTRUCTION ON BLOCKLAYING STUDENTS’ ACHIEVEMENT AND RETENTION IN TECHNICAL COLLEGES (NAU Journal of Technology and Vocational Education, 2024)
This study examined the interactive effect of gender and mother tongue for instruction ontechnical college students’ achievement and retention in blocklaying in Oyo central senatorialdistrict technical colleges. Two research questions were raised, and were hypothesized andtested at 0.05 level of significance. Quasi-experimental research design involving a pre-testpost-test non-equivalent control group design was adopted for the study. The population of thestudy was 461 parts 1 to 3 students offering blocklaying in the three technical colleges acrossthe senatorial district. Sample of 83 students was drawn for the study, using purposive samplingtechnique. The instrument used to collect data was a Blocklaying Achievement Test (BCAT),which was validated by three experts. Kuder Richardson 20 was used to establish the reliabilitycoefficient of 0.82 for the BCAT. For the test of hypotheses, ANCOVA was employed. Findingsrevealed significant interaction effects of mother tongue medium of instruction and gender onthe students’ achievement and retention.
Keywords: Blocklaying, achievement, retention, Yoruba, English, mother tongue, gender